Laminate and image display device

JP2023154554A5Pending Publication Date: 2025-03-26SUMITOMO CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022063946
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-07
Publication Date
2025-03-26

AI Technical Summary

Technical Problem

Ultra-thin glass front plates in image display devices are prone to cracking when bonded to optical members and bent, compromising handling and flexibility.

Method used

A laminate structure comprising ultra-thin glass, an adhesive layer with a storage modulus of 0.2 MPa or less at 25°C, and a polarizing film made of a cured liquid crystal layer, with specific thickness and modulus ranges for each component, enhancing flexibility and handling properties.

Benefits of technology

The laminate exhibits improved flexibility, allowing for repeated bending without cracking, with a bending radius of 4 mm or less and up to 500,000 bends, suitable for flexible displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a laminate which comprises a front plate having an ultra-thin glass, an adhesive layer, and a polarizing film and offers improved handleability and fixability.SOLUTION: A laminate is provided, comprising a front plate, adhesive layer, and polarizing film arranged in the described order, the front plate comprising an ultra-thin glass and hard coat layer, the adhesive layer having a storage modulus of 0.2 MPa or less at 25°C, and the polarizing film being composed of a cured liquid crystal layer containing a cured product of a polymerizable liquid crystal compound.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate, and more particularly to an image display device including the laminate.

Background Art

[0002] Patent Document 1 proposes a glass substrate laminate in which a hard coat layer is provided on a thin glass as a flexible glass substrate for a window of a flexible display.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0004] A front panel having an ultra-thin glass may be prone to cracking when bonded to an optical member, and when the image display device is bent after being incorporated into the image display device. <图注:

[0005] <图注: An object of the present invention is to provide a laminate including a front panel having an ultra-thin glass, an adhesive layer, and a polarizing film, which has improved handling properties and improved flexibility.

Means for Solving the Problems

[0006] The present invention provides the following laminate and image display device. [1] A laminate including a front panel, an adhesive layer, and a polarizing film in this order, wherein the front panel includes an ultra-thin glass and a hard coat layer, the storage elastic modulus of the adhesive layer at 25°C is 0.2 MPa or less, and the polarizing film is composed of a liquid crystal cured layer including a cured product of a polymerizable liquid crystal compound. [2] The laminate described in [1], wherein the thickness of the ultrathin glass is 50 μm or less. [3] The laminate according to [1], wherein the thickness of the hard coat layer is 10 μm or more. [4] The laminate according to [2], wherein the thickness of the hard coat layer is 10 μm or more. [5] The laminate according to [1] to [4], wherein the storage modulus of the adhesive layer at a temperature of 25°C is 0.01 MPa or more. [6] The laminate according to any one of [1] to [4], wherein the thickness of the adhesive layer is 30 μm or less. [7] The laminate according to [5], wherein the thickness of the adhesive layer is 30 μm or less. [8] An image display device comprising a laminate as described in any of [1] to [4]. [9] An image display device comprising the laminate described in [5].

[10] An image display device including the laminate described in [6].

[11] [7] An image display device including the laminate described above.

[0007] The present invention further provides the following laminates and image display devices. [a] The front panel, adhesive layer, and polarizing film are included in this order, The aforementioned front panel includes an ultra-thin glass and a hard coat layer. The storage modulus of the adhesive layer at a temperature of 25°C is 0.2 MPa or less. The polarizing film is a laminate composed of a liquid crystal curing layer containing a cured polymerizable liquid crystal compound. [b] The laminate described in [a], wherein the thickness of the ultrathin glass is 50 μm or less. [c] The laminate according to [a] or [b], wherein the thickness of the hard coat layer is 10 μm or more. [d] The laminate according to any one of [a] to [c], wherein the storage modulus of the adhesive layer at a temperature of 25°C is 0.01 MPa or more. [e] The laminate according to any one of [a] to [d], wherein the thickness of the adhesive layer is 30 μm or less. An image display device including the laminate according to any one of [a] to [e] in [f].

Advantages of the Invention

[0008] According to the present invention, it is possible to provide a laminate including a front panel having an ultra-thin glass, an adhesive layer, and a polarizing film, the handling property of which is improved and the flexibility of which is enhanced.

Brief Description of the Drawings

[0009] [Figure 1] It is a schematic cross-sectional view showing an example of the layer structure of the laminate according to the present invention. [Figure 2] It is a schematic cross-sectional view showing another example of the layer structure of the laminate according to the present invention. [Figure 3] It is a schematic cross-sectional view showing another example of the layer structure of the laminate according to the present invention. [Figure 4] It is a schematic view explaining a method of a flexibility test.

Modes for Carrying Out the Invention

[0010] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiments. In all the following drawings, the scale is appropriately adjusted for easy understanding of each component, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.

[0011] <Laminate> The laminate according to one aspect of the present invention includes a front panel, an adhesive layer, and a polarizing film in this order, the front panel includes an ultra-thin glass and a hard coat layer, the storage elastic modulus of the adhesive layer at 25°C is 0.2 MPa or less, and the polarizing film is a laminate composed of a liquid crystal cured layer containing a cured product of a polymerizable liquid crystal compound.

[0012] Fig. 1 shows a schematic cross-sectional view of a laminate according to one embodiment of the present invention. In the laminate 100 shown in Fig. 1, a front panel 10, an adhesive layer 11, and a polarizing plate 12 are laminated in this order. The adhesive layer 11 may be disposed in contact with the front panel 10 and the polarizing plate 12. The front panel 10 includes an ultra-thin glass 14 and a hard coat layer 13. The polarizing plate 12 has a base film 15, an alignment film 16, a polarizing film 17, and a protective layer 18 laminated in order from the viewing side (the front panel 10 side). In addition to the above-described layers, the laminate 100 may further include other layers such as a retardation plate, a bonding layer, an organic EL panel, a touch sensor, and the like.

[0013] The laminate 100 can be bent with the front panel 10 side being inside or outside with respect to the bending axis, preferably with the front panel 10 side being inside with respect to the bending axis. Being able to be bent means that it can be bent without causing cracks in the laminate. Bending includes a form of folding in which a curved surface is formed in the bent portion. In the form of folding, the bending radius of the inner surface of the fold is not particularly limited. Also, bending includes a form of refraction in which the refraction angle of the inner surface is greater than 0° and less than 180°, and a form of folding in which the bending radius of the inner surface is approximated to zero or the refraction angle of the inner surface is 0°. Since the laminate of the present invention can be bent, it is suitable for a flexible display.

[0014] When the laminate 100 is repeatedly bent in the evaluation of bendability described below, the bending radius at which cracks are unlikely to occur may be, for example, 4 mm or less, preferably 2 mm or less, more preferably 1.5 mm or less. When the laminate 100 is repeatedly bent with a bending radius of 1.5 mm in the evaluation of bendability described below, the number of bending times until cracks first occur is preferably 200,000 times or more, more preferably 300,000 times or more, still more preferably 400,000 times or more, and particularly preferably 500,000 times or more.

[0015] The thickness of the laminate 100 is not particularly limited, as it varies depending on the function required of the laminate and its application, but is, for example, 30 μm or more and 4000 μm or less, preferably 2000 μm or less, and more preferably 1000 μm or less. In this specification, the thickness of the laminate and each layer can be measured according to the thickness measurement method described in the examples later.

[0016] The planar shape of the laminate 100 may be, for example, a square shape, preferably a square shape having a long side and a short side, and more preferably a rectangle. When the planar shape of the laminate 100 is a rectangle, the length of the long side may be, for example, 10 mm or more and 1400 mm or less, and preferably 600 mm or less. The length of the short side may be, for example, 5 mm or more and 800 mm or less, preferably 500 mm or less, and more preferably 300 mm or less. Each layer constituting the laminate may have rounded corners, notched ends, or perforated ends.

[0017] (Front plate) The front panel 10 constitutes the outermost surface on the viewing side of the image display device and can have the function of protecting the front (screen) of the image display device. The front panel 10 may be what is called a window film. The front panel 10 includes an ultra-thin glass 14 and a hard coat layer 13. The hard coat layer may be placed on only one side of the ultra-thin glass or on both sides of the ultra-thin glass. In this specification, glass with a thickness of 50 μm or less is referred to as ultra-thin glass.

[0018] The thickness of the front panel 10 may be, for example, 30 μm or more and 200 μm or less, preferably 100 μm or less, and more preferably 50 μm or less.

[0019] The ultra-thin glass 14 can have a thickness of, for example, 50 μm or less. By using ultra-thin glass with a thickness of 50 μm or less, the laminate can be made thinner, and the flexibility and light transmittance of the laminate tend to be improved. The thickness of the ultra-thin glass 14 is preferably 45 μm or less, more preferably 40 μm or less, even more preferably 35 μm or less, and particularly preferably 30 μm or less. The thickness of the ultra-thin glass 14 is usually 10 μm or more, and preferably 15 μm or more from the viewpoint of improving the impact resistance of the laminate.

[0020] It is preferable to use chemically strengthened glass for the ultra-thin glass 14, which has excellent strength and light transmittance. By using chemically strengthened glass, the impact resistance of the laminate can be improved while maintaining flexibility. Chemically strengthened glass can be obtained by chemical ion exchange treatment of glass. Chemical ion exchange treatment can improve the strength of the glass surface by partially replacing sodium ions and lithium ions on the glass surface with potassium ions, which have a larger ionic radius. Surface strength is improved by forming a thin compressive stress layer. Examples of glass used for chemically strengthened glass include aluminosilicate glass, soda-lime glass, borosilicate glass, lead glass, alkali barium glass, and aluminoborosilicate glass.

[0021] Chemical ion exchange treatment can be performed by immersing the glass in an ion exchange solution heated above its melting point, or by directly applying a paste-like ion exchange solution to the glass. Examples of ion exchange solutions include those based on potassium nitrate, potassium carbonate, potassium bicarbonate, potassium phosphate, potassium sulfate, and potassium hydroxide. Among these, potassium nitrate (330°C) is preferred because its melting point is lower than that of glass (usually between 500°C and 600°C) and it is easy to handle.

[0022] The glass may be thinned by etching before the chemical ion exchange treatment. The etching treatment can also be carried out using hydrofluoric acid or a mixture thereof with an aqueous solution of ammonium fluoride and an organic acid, such as formic acid, acetic acid, or propionic acid, as the chemical treatment solution. Etching can be performed using these by spraying, dipping, etc. The etching treatment may also be carried out using He gas or Ar gas containing at least one fluorine-containing inert gas, such as CF4, C3F8, C2F6, or XeF2, as the etching gas. Specifically, etching can be performed by plasma-generating a fluorine-containing inert gas diluted with He gas or Ar gas under atmospheric pressure to liberate fluorine from carbon fluoride.

[0023] The front panel 10 has a hard coat layer 13 on at least one surface of the ultra-thin glass 14. Providing the hard coat layer 13 tends to improve the handling of the laminate 100. In addition, providing the hard coat layer 13 can improve hardness and scratch resistance. When the image display device on which the front panel 10 is placed is a touch panel type image display device, the surface of the front panel becomes the touch surface, so a front panel 10 having a hard coat layer 12 is preferable.

[0024] The hard coat layer 13 may be formed on one surface of the ultrathin glass 14, or on both surfaces. When formed on both surfaces of the ultrathin glass 14, the handling of the laminate 100 tends to improve. When the hard coat layer 13 is formed on one surface of the ultrathin glass 14, it is preferable that it be formed on the surface that will be visible when the laminate 100 is bonded to an image display device.

[0025] The hard coat layer 13 can be, for example, a cured layer of an ultraviolet-curable resin. Examples of ultraviolet-curable resins include (meth)acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, epoxy resins, and the like. The hard coat layer 13 may contain additives to improve hardness. The additives are not limited to inorganic fine particles, organic fine particles, or mixtures thereof.

[0026] The hard coat layer 13 may have a single-layer structure or a multilayer structure consisting of two or more layers. When the hard coat layer 13 has a multilayer structure, the handling properties of the laminate tend to improve. When the hard coat layer 13 has a multilayer structure, the thickness of each layer and the materials constituting each layer may be different from each other or the same. The multilayer structure may consist of two or three layers, and preferably consists of two layers.

[0027] The thickness of the hard coat layer 13 may be, for example, 10 μm or more, preferably 15 μm or more, more preferably 20 μm or more, and may be, for example, 50 μm or less, 40 μm or less, or 30 μm or less.

[0028] When the hard coat layer 13 has a multilayer structure or is arranged on both sides of the ultrathin glass, the total thickness of all hard coat layers may be, for example, 10 μm or more, preferably 15 μm or more, more preferably 20 μm or more, and may be, for example, 50 μm or less, 40 μm or less, or 30 μm or less.

[0029] On the visible side of the hard coat layer 13, it is preferable to have an abrasion-resistant layer formed to improve abrasion resistance and prevent contamination by sebum, etc. The front plate 10 may have an abrasion-resistant layer, and the abrasion-resistant layer may be a layer constituting the visible surface of the front plate 10. The abrasion-resistant layer may include a structure derived from a fluorine compound. Preferably, the fluorine compound has silicon atoms and the silicon atoms have hydrolyzable groups such as alkoxy groups or halogens. The hydrolyzable groups can form a coating film through a dehydration condensation reaction and can also improve the adhesion of the abrasion-resistant layer by reacting with active hydrogen on the substrate surface. Furthermore, it is preferable that the fluorine compound has a perfluoroalkyl group or a perfluoropolyether structure, as this can impart water repellency. Particularly preferred are fluorine-containing polyorganosiloxane compounds having a perfluoropolyether structure and a long-chain alkyl group with 4 or more carbon atoms. It is also preferable to use two or more types of fluorine compounds. Further preferred fluorine compounds include fluorine-containing organosiloxane compounds containing alkylene groups with 2 or more carbon atoms and perfluoroalkylene groups.

[0030] The thickness of the wear-resistant layer may be, for example, 1 nm to 20 nm. The wear-resistant layer is also water-repellent, with a water contact angle of, for example, 110 to 125°. The contact angle hysteresis and sliding angle measured by the sliding method are approximately 3 to 20° and 2 to 55°, respectively. Furthermore, the wear-resistant layer may contain various additives, such as silanol condensation catalysts, antioxidants, rust inhibitors, ultraviolet absorbers, light stabilizers, antifungal agents, antibacterial agents, anti-bacterial agents, deodorants, pigments, flame retardants, and antistatic agents, to the extent that they do not hinder the effects of the present invention.

[0031] A primer layer may be provided between the wear-resistant layer and the hard coat layer. Examples of primers include UV-curing, thermosetting, moisture-curing, or two-component epoxy compounds. Alternatively, polyamic acid may be used as the primer, and silane coupling agents are also preferred. The thickness of the primer layer is, for example, 0.001 to 2 μm.

[0032] A front panel containing an abrasion-resistant layer and a hard coat layer can be formed by first applying, drying, and curing a primer agent on the hard coat layer as needed to form a primer layer, and then applying and drying a composition containing a fluorine compound (abrasion-resistant layer coating composition). Examples of application methods include dip coating, roll coating, bar coating, spin coating, spray coating, die coating, and gravure coating. It is also preferable to perform a hydrophilization treatment such as plasma treatment, corona treatment, or ultraviolet treatment on the coating surface before applying the primer agent or the abrasion-resistant layer coating composition.

[0033] The front panel 10 may be equipped with a resin film to enhance impact resistance. The resin film is not limited as long as it is a light-transmitting resin film. For example, films made of polymers such as triacetylcellulose, acetylcellulose butyrate, ethylene-vinyl acetate copolymer, propionylcellulose, butyrylcellulose, acetylpropionylcellulose, polyester, polystyrene, polyamide, polyetherimide, poly(meth)acrylic, polyimide, polyethersulfone, polysulfone, polyethylene, polypropylene, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl acetal, polyether ketone, polyetherether ketone, polymethyl(meth)acrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, and polyamideimide can be used. These polymers can be used individually or in mixtures of two or more. When the laminate is used in a flexible display, a resin film made of polymers such as polyimide, polyamide, and polyamideimide is preferably used, as it can be configured to have excellent flexibility, high strength, and high transparency. In this specification, "(meth)acrylic" means either acrylic or methacrylic. The "(meth)" in (meth)acrylate, etc., has the same meaning. The thickness of the resin film is, for example, 10 μm or more and 500 μm or less, preferably 20 μm or more and 100 μm or less.

[0034] (Adhesive layer) The adhesive layer 11 may be an interposed layer between the front plate 10 and the polarizing plate 12, joining them together. The adhesive layer may be, for example, a layer composed of an adhesive or a layer that has been treated in some way. The adhesive is also called a pressure-sensitive adhesive. In this specification, "adhesive" refers to an adhesive other than the adhesive (pressure-sensitive adhesive), and is clearly distinguished from the adhesive. The adhesive layer may be a single layer or consist of two or more layers, but is preferably a single layer.

[0035] The storage modulus of the adhesive layer 11 at a temperature of 25°C is 0.2 MPa or less, preferably 0.1 MPa or less, and more preferably 0.05 MPa or less. The storage modulus of the adhesive layer 11 at a temperature of 25°C is measured according to the measurement method described in the Examples section below. A storage modulus of 0.2 MPa or less for the adhesive layer 11 at a temperature of 25°C tends to improve the flexibility of the laminate 100.

[0036] The adhesive layer 11 is formed from an adhesive composition described later. The storage modulus of the adhesive layer 11 at a temperature of 25°C can be adjusted by, for example, selecting the type of monomer constituting the (meth)acrylic polymer contained in the adhesive composition, adjusting the molecular weight of the (meth)acrylic polymer, adjusting the crosslinking density by adding a crosslinking agent, adjusting the thickness of the adhesive layer, or by a combination of these methods. It is also possible to select and use a commercially available adhesive that has the desired storage modulus.

[0037] The adhesive layer 11 can be composed of an adhesive composition mainly composed of resins such as (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether. Among these, an adhesive composition using a (meth)acrylic resin as the base polymer, which has excellent transparency, weather resistance, and heat resistance, is preferred. The adhesive composition may be of the active energy ray curing type or thermosetting type.

[0038] As the (meth)acrylic resin (base polymer) used in the adhesive composition, polymers or copolymers using one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, are preferably used. It is preferable to copolymerize polar monomers into the base polymer. Examples of polar monomers include monomers having carboxyl groups, hydroxyl groups, amide groups, amino groups, epoxy groups, etc., such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.

[0039] The adhesive composition may contain only the above-mentioned base polymer, but usually further contains a crosslinking agent. Examples of crosslinking agents include divalent or higher metal ions that form metal carboxylate salts with carboxyl groups; polyamine compounds that form amide bonds with carboxyl groups; polyepoxy compounds or polyols that form ester bonds with carboxyl groups; and polyisocyanate compounds that form amide bonds with carboxyl groups. Among these, polyisocyanate compounds are preferred.

[0040] An active energy ray curable adhesive composition is an adhesive composition that has the property of curing when irradiated with active energy rays such as ultraviolet rays or electron beams. It can adhere to a substrate such as a film even before irradiation with active energy rays, and the adhesion strength can be adjusted by curing with irradiation with active energy rays. The active energy ray curable adhesive composition is preferably ultraviolet curable. In addition to a base polymer and a crosslinking agent, the active energy ray curable adhesive composition further contains an active energy ray polymerizable compound. Furthermore, it may also contain a photopolymerization initiator and a photosensitizer as needed.

[0041] The adhesive composition may contain additives such as fine particles for light scattering, beads (resin beads, glass beads, etc.), glass fibers, resins other than the base polymer, tackifiers, fillers (metal powders and other inorganic powders, etc.), antioxidants, UV absorbers, dyes, pigments, colorants, defoamers, corrosion inhibitors, antistatic agents, and photopolymerization initiators.

[0042] The adhesive layer 11 can be formed by applying a diluted organic solvent solution of the adhesive composition onto a substrate and drying it. When an active energy ray-curable adhesive composition is used, the formed adhesive layer can be irradiated with active energy rays to produce a cured product with a desired degree of curing.

[0043] The thickness of the adhesive layer 11 is preferably, for example, 1 μm or more and 100 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, and may be 10 μm or more or more.

[0044] [Polarizing film] The polarizing film 17 is composed of a liquid crystal cured layer containing a cured polymerizable liquid crystal compound. The composition of the polarizing film 17 with a liquid crystal cured layer containing a cured polymerizable liquid crystal compound tends to improve the flexibility of the laminate 100. The liquid crystal cured layer containing a cured polymerizable liquid crystal compound may be a polarizing layer obtained by coating a base film with a composition containing a polymerizable dichroic dye having liquid crystal properties, or a composition containing a polymerizable liquid crystal compound and a dichroic dye, and curing it. Specifically, iodine and dichroic organic dyes are used as dichroic dyes. Examples of dichroic organic dyes include azo dyes. Azo dyes include, for example, dichroic direct dyes made from disazo compounds such as CIDIRECT RED 39, and dichroic direct dyes made from compounds such as trisazo and tetrakisazo.

[0045] The base film may have an alignment film on one side. The polarizing film 17 is preferably a layer comprising a cured product of a composition containing a polymerizable liquid crystal compound and one or more azo dyes, and an alignment film, from the viewpoint of improving flexibility. The thickness of the alignment film may be, for example, 5 nm or more and 1 μm or less.

[0046] The polarizing film 17 may be incorporated into the laminate together with the base film, provided that a liquid crystal cured layer containing a cured polymerizable liquid crystal compound is incorporated into the laminate. The material and thickness of the base film may be the same as those of the thermoplastic resin film described later. The base film may have a hard coat layer (HC layer) formed on at least one surface as a protective layer, as described later.

[0047] The thickness of the liquid crystal cured layer containing the cured polymerizable liquid crystal compound is typically 10 μm or less, preferably 8 μm or less, and more preferably 5 μm or less.

[0048] [Protective layer] The protective layer is disposed on one or both sides of the polarizing film 17 and may have the function of protecting the surface of the polarizing film 17. In this specification, a polarizing film with a laminated protective layer may be referred to as a polarizing plate.

[0049] The protective layer can be an organic layer or an inorganic layer. The organic or inorganic layer can be a layer formed by coating. The organic layer can be a cured resin layer, such as a protective layer-forming composition, for example, a (meth)acrylic resin composition, an epoxy resin composition, or a polyimide resin composition. The protective layer-forming composition may be an active energy ray curing type or a thermosetting type. The inorganic layer can be formed from, for example, silicon oxide. When the protective layer is an organic layer, it may also be called a hard coat layer (HC layer) or an overcoat (OC) layer. The protective layer may be formed directly on the substrate film described above, or it may be formed directly on the polarizing film. The protective layer may be formed on the substrate film described above, and then the polarizing film may be formed.

[0050] When the protective layer is an organic layer, for example, the protective layer can be produced by applying an active energy ray curable protective layer-forming composition onto a base film and curing it by irradiating it with active energy. The base film is as described above. The protective layer can be incorporated into the laminate after the base film has been peeled off and removed. Examples of methods for applying the protective layer-forming composition include spin coating. When the protective layer is an inorganic layer, the protective layer can be formed by methods such as sputtering or vapor deposition. When the protective layer is an organic or inorganic layer, the thickness of the protective layer may be, for example, 0.1 μm or more and 10 μm or less, preferably 5 μm or less.

[0051] As a protective layer, for example, a thermoplastic resin film with excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, and stretchability can be used. Specific examples of such thermoplastic resins include cellulose resins such as triacetylcellulose; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamides; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having cyclo and norbornene structures (also called norbornene-based resins); (meth)acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins; and mixtures thereof. When protective layers are laminated on both sides of the polarizing film 17, the two protective layers may be of the same type or different types. From the viewpoint of thinning, the thickness of the thermoplastic resin film is usually 300 μm or less, preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, and still more preferably 30 μm or less, and is usually 1 μm or more, for example 5 μm or more or 20 μm or more.

[0052] If the protective layer is a thermoplastic resin film, the thermoplastic resin film can be laminated onto the polarizing film 17 via a laminating layer described later. The laminating layer for bonding the thermoplastic resin film to the polarizing film 17 is preferably an adhesive layer. Alternatively, a polarizing layer can be formed on top of the protective layer described above. The laminate 100 preferably has at least one protective layer selected from the group consisting of a thermoplastic resin film and a cured resin layer on the side of the polarizing film 17 opposite to the adhesive layer 11.

[0053] [Other layers] (phase plate) The laminate 100 may have a phase difference plate on the side opposite to the adhesive layer 11 of the polarizing plate 12 via a bonding layer described later. The phase difference plate may include a cured layer of polymerizable liquid crystal compound. The cured layer of polymerizable liquid crystal compound can be formed by applying a phase difference layer forming composition containing the polymerizable liquid crystal compound to a substrate film and curing it. Examples of application methods include coating methods and printing methods. Examples of coating methods include bar coating, knife coating, blade coating, die coating, direct gravure coating, reverse gravure coating, roll coating, CAP coating, spin coating, spray coating, screen coating, slit coating, and dip coating. Examples of printing methods include offset printing, gravure printing, screen printing, and inkjet printing.

[0054] The cured layer of the polymerizable liquid crystal compound can be a phase difference layer. The phase difference layer can consist of one or more layers. The phase difference layer may be a positive A plate such as a λ / 4 plate or a λ / 2 plate, and a positive C plate. If the phase difference plate contains only one cured layer of the polymerizable liquid crystal compound, the phase difference layer is preferably a λ / 4 plate. If the phase difference plate contains two cured layers of the polymerizable liquid crystal compound, the phase difference layer can be a phase difference layer laminate consisting of a first liquid crystal cured phase difference layer and a second liquid crystal cured phase difference layer. The first liquid crystal cured phase difference layer and the second liquid crystal cured phase difference layer may be laminated via a bonding layer described later, preferably via an adhesive layer. Preferably, the combinations of the first liquid crystal cured phase difference layer and the second liquid crystal cured phase difference layer are a combination in which the first liquid crystal cured phase difference layer is a λ / 4 plate and the second liquid crystal cured phase difference layer is a λ / 2 plate, and a combination in which the first liquid crystal cured phase difference layer is a λ / 4 plate and the second liquid crystal cured phase difference layer is a positive C plate. In this specification, a polarizing plate in which phase difference layers are laminated is sometimes referred to as a circular polarizing plate.

[0055] The thickness of the cured layer of the polymerizable liquid crystal compound is, for example, 0.1 μm or more and 10 μm or less, preferably 8 μm or less, and more preferably 6 μm or less.

[0056] An alignment layer may be formed between the base film and the cured layer of the polymerizable liquid crystal compound. The material and thickness of the base film may be the same as those of the thermoplastic resin film described above. The phase difference layer, which is formed by curing the polymerizable liquid crystal compound, may be incorporated into the laminate 100 together with either the alignment layer or the base film, or both. The thickness of the alignment layer may be, for example, 5 nm or more and 1 μm or less.

[0057] (Bonding layer) The laminating layer is a layer composed of an adhesive or bonding agent. The laminating layer can be, for example, a layer for laminating a polarizing film and a phase difference plate, a layer for laminating a laminate and an organic EL panel or touch sensor panel, a layer for joining a polarizing film and a protective layer, a layer for joining a first liquid crystal cured phase difference layer and a second liquid crystal cured phase difference layer, etc. The adhesive constituting the laminating layer may be the same agent as exemplified for the adhesive composition constituting the adhesive layer described above, or it may be a different adhesive, such as a (meth)acrylic adhesive, a styrene adhesive, a silicone adhesive, a rubber adhesive, a urethane adhesive, a polyester adhesive, an epoxy copolymer adhesive, etc. The laminate 100 may have one laminating layer or two or more. If the laminate 100 has multiple laminating layers, the multiple laminating layers may be the same as or different from each other.

[0058] The adhesive constituting the bonding layer can be formed by combining one or more types from, for example, water-based adhesives, active energy ray-curable adhesives, and adhesives. Examples of water-based adhesives include aqueous solutions of polyvinyl alcohol-based resins and two-component water-based urethane emulsion adhesives. Examples of active energy ray-curable adhesives are adhesives that harden when irradiated with active energy rays such as ultraviolet light, and include those containing polymerizable compounds and photopolymerization initiators, those containing photoreactive resins, and those containing binder resins and photoreactive crosslinking agents. Examples of polymerizable compounds include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, as well as oligomers derived from these monomers. Examples of photopolymerization initiators include substances that generate active species such as neutral radicals, anionic radicals, and cationic radicals when irradiated with active energy rays such as ultraviolet light.

[0059] When an adhesive layer is used as the bonding layer, it is preferably 1 μm or more thick, may be 5 μm or more, and is usually 200 μm or less, for example, 150 μm or less or 100 μm or less. When an adhesive layer is used as the bonding layer, the thickness of the bonding layer is preferably 0.1 μm or more, may be 0.5 μm or more, preferably 10 μm or less, and may be 5 μm or less.

[0060] (OLED panel) The organic EL panel can be any known organic EL panel. The laminate 100 may have an organic EL panel on the side of the polarizing plate 12 opposite to the adhesive layer 11. If the laminate 100 has a phase difference plate on the side of the adhesive layer 11 opposite to the polarizing plate 12, the organic EL panel may be positioned on the side of the phase difference plate opposite to the polarizing plate 12.

[0061] (Touch sensor panel) A touch sensor panel is not limited to any sensor capable of detecting the touched position, and examples include resistive, capacitive, optical, ultrasonic, electromagnetically coupled, and surface acoustic wave touch sensor panels. Among these, capacitive touch sensor panels are preferred due to their low cost, fast response speed, and thin-film capability. A touch sensor panel may include an adhesive layer, a separation layer, a protective layer, etc., between the transparent conductive layer and the substrate film supporting it. Examples of adhesive layers include adhesive layers and tack layers. Examples of substrate films supporting the transparent conductive layer include a substrate film on which the transparent conductive layer is vapor-deposited on one surface, and a substrate film on which the transparent conductive layer is transferred via an adhesive layer.

[0062] An example of a capacitive touch sensor panel consists of a base film, a transparent conductive layer for position detection provided on the surface of the base film, and a touch position detection circuit. In an image display device equipped with a laminate having a capacitive touch sensor panel, when the surface of the front panel is touched, the transparent conductive layer is grounded at the touched point via the capacitance of the human body. The touch position detection circuit detects the grounding of the transparent conductive layer, and the touched position is detected. By having multiple transparent conductive layers spaced apart from each other, more detailed position detection becomes possible.

[0063] The transparent conductive layer may be a transparent conductive layer made of a metal oxide such as ITO, or a metal layer made of a metal such as aluminum, copper, silver, gold, or an alloy thereof. The transparent electrode layer is formed by a coating method such as sputtering, printing, or vapor deposition. A photosensitive resist is formed on the transparent electrode layer, and then an electrode pattern layer is formed by photolithography. Negative-type or positive-type photosensitive resist is used, and the photosensitive resist may remain or be removed after patterning. When forming the film by sputtering, a mask with the electrode pattern shape can be placed and sputtering performed to form the electrode pattern layer.

[0064] The separation layer is formed on a substrate such as glass and serves to separate the transparent conductive layer formed on the separation layer from the substrate together with the separation layer. The separation layer is preferably an inorganic layer or an organic layer. Examples of materials for forming the inorganic layer include silicon oxide. Examples of materials for forming the organic layer include (meth)acrylic resin compositions, epoxy resin compositions, polyimide resin compositions, etc. The separation layer can be formed by coating using a known coating method and curing by heat curing, UV curing, or a combination thereof.

[0065] A protective layer may be provided in contact with the transparent conductive layer to protect it. The protective layer includes at least one of an organic insulating film and an inorganic insulating film, and these films can be formed by coating methods such as spin coating, sputtering, or vapor deposition.

[0066] The insulating layer can be formed from, for example, an inorganic insulating material such as silicon oxide, or a transparent organic material such as acrylic resin. The insulating layer can be formed by applying it using a known coating method, followed by thermosetting, UV curing, heat drying, vacuum drying, etc.

[0067] Examples of resin films for the base film of the touch sensor panel include triacetylcellulose, polyethylene terephthalate, cycloolefin polymer, polyethylene naphthalate, polyolefin, polycycloolefin, polycarbonate, polyethersulfone, polyarylate, polyimide, polyamide, polystyrene, and polynorbornene. From the viewpoint of easily forming a base film with the desired toughness, polyethylene terephthalate is preferably used.

[0068] The base film of the touch sensor panel is preferably 50 μm or less in thickness, and more preferably 30 μm or less, from the viewpoint of easily forming a laminate with excellent flexibility. The thickness of the base film of the touch sensor panel may be, for example, 5 μm or more.

[0069] A touch sensor panel can be manufactured, for example, as follows. In the first method, a base film is first laminated onto a substrate via an adhesive layer. A transparent conductive layer, patterned by photolithography, is formed on the base film. By applying heat, the substrate and the base film are separated to obtain a touch sensor panel consisting of the transparent conductive layer and the base film. The substrate is not particularly limited as long as it maintains flatness and has heat resistance, but a glass substrate is preferred.

[0070] In the second method, first, a material for forming a separation layer is applied to the substrate to form the separation layer. If necessary, a protective layer is formed on the separation layer by coating. The protective layer may be formed so as not to be formed in the area where the pad pattern layer is formed. A transparent conductive layer, patterned by photolithography, is formed on the separation layer (or protective layer). An insulating layer is formed on the transparent conductive layer so as to fill the electrode pattern layer. A protective film is laminated on the insulating layer with a peelable adhesive, transferring from the insulating layer to the separation layer and separating the substrate. By peeling off the peelable protective film, a touch sensor panel having the insulating layer / transparent conductive layer / (protective layer) / separation layer in this order is obtained.

[0071] When a base film is included, the thickness of the touch sensor panel may be, for example, 5 μm or more and 2000 μm or less, or 5 μm or more and 100 μm or less.

[0072] When the base film is not included, the thickness of the touch sensor panel is, for example, 0.5 μm or more and 10 μm or less, preferably 5 μm or less.

[0073] If the laminate 100 includes a touch sensor panel, the touch sensor panel can be placed, for example, between the phase difference plate and the organic EL panel, or between the front plate 10 and the polarizing plate 12.

[0074] [Layer structure of the laminate] The laminate 200 shown in Figure 2 has the front plate 21, adhesive layer 22, polarizing plate 23, bonding layer 24, and phase difference plate 25 laminated in this order from the viewing side. The front plate 21 has the first hard coat layer 26, the second hard coat layer 27, and the ultra-thin glass 28 laminated in this order from the viewing side. The polarizing film 23 has the base film 29, alignment film 30, polarizing film 31, and protective layer 32 laminated in this order from the viewing side. The phase difference plate 25 has the first liquid crystal cured phase difference layer 33 and the second liquid crystal cured phase difference layer 34 laminated in this order from the viewing side.

[0075] Figure 3 shows the layer structure of the laminate 300. In Figure 3, the explanation for each layer is the same as the explanation for the layer with the same reference numeral in Figure 2. The laminate 300 has the same layer structure as the laminate 200 described above, except that the first hard coat layer 26, the ultra-thin glass 28, and the second hard coat layer 27 are laminated in that order.

[0076] [Applications of laminates] The laminate 100 can be used, for example, in an image display device. The image display device is not particularly limited and includes, for example, an organic electroluminescent (organic EL) display device, an inorganic electroluminescent (inorganic EL) display device, a liquid crystal display device, a field-emitting light display device, etc. The image display device may have a touch panel function. The image display device can preferably be a flexible display. The laminate 100 may be arranged in the image display device such that the front plate 10 side is the viewing side with respect to the adhesive layer 11, and preferably the front plate 11 constitutes the outermost surface of the image display device.

[0077] [Method for manufacturing laminates] The laminate can be manufactured by a method that includes a step of bonding the layers constituting the laminate together via an adhesive layer or a further adhesive layer. When bonding the layers together via an adhesive layer or an adhesive layer, it is preferable to apply a surface activation treatment, such as corona treatment, to one or both of the bonding surfaces in order to improve adhesion.

[0078] A liquid crystal cured layer containing a cured polymerizable liquid crystal compound constituting a polarizing film can be formed on a substrate via an alignment film. The liquid crystal cured layer containing a cured polymerizable liquid crystal compound can be formed by applying and curing a liquid crystal cured layer forming composition containing a dichroic dye and a polymerizable liquid crystal compound. In addition to the dichroic dye and polymerizable liquid crystal compound mentioned above, the liquid crystal cured layer forming composition preferably further contains a polymerization initiator, a leveling agent, and a solvent, and may further contain a photosensitizer, a polymerization inhibitor, a leveling agent, and the like.

[0079] The phase difference layer contained in the phase difference plate can be manufactured by applying a phase difference layer-forming composition containing a polymerizable liquid crystal compound to a substrate and, if present, an alignment film, and polymerizing the polymerizable liquid crystal compound. The phase difference layer-forming composition further contains a solvent, a polymerization initiator, and may further contain a photosensitizer, a polymerization inhibitor, a leveling agent, etc. The substrate and the alignment film may be incorporated into the phase difference plate, or they may be peeled off from the phase difference plate and not become components of the laminate.

[0080] The coating, drying, and polymerization of the liquid crystal curing layer-forming composition and the phase difference layer-forming composition can be carried out by conventionally known coating, drying, and polymerization methods.

[0081] For example, methods for applying the liquid crystal hardening layer composition and the phase difference layer composition can include wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, and die coating.

[0082] The polymerization method for polymerizable liquid crystal compounds can be selected according to the type of polymerizable group in the polymerizable liquid crystal compound. If the polymerizable group is a photopolymerizable group, polymerization can be performed by photopolymerization. If the polymerizable group is a thermopolymerizable group, polymerization can be performed by thermopolymerization. In the manufacturing method of this embodiment, photopolymerization is preferred. Photopolymerization does not necessarily require heating the transparent substrate to a high temperature, so a transparent substrate with low heat resistance can be used. Photopolymerization is performed by irradiating a film made of a liquid crystal curing layer forming composition or a phase difference layer forming composition containing a polymerizable liquid crystal compound with visible light or ultraviolet light. Ultraviolet light is preferred because it is easier to handle.

[0083] The adhesive layer can be prepared as an adhesive sheet. The adhesive sheet can be manufactured by, for example, dissolving or dispersing an adhesive composition in an organic solvent such as toluene or ethyl acetate to prepare an adhesive liquid, forming a sheet of adhesive on a release film that has been treated for mold release, and then laminating another release film onto the adhesive layer. The layers can be laminated by laminating the adhesive sheet, from which one release film has been peeled off, to one layer, then peeling off the other release film and laminating the other layer.

[0084] For applying the adhesive liquid onto the release film, conventional coating techniques such as die coaters, comma coaters, reverse roll coaters, gravure coaters, rod coaters, wire bar coaters, doctor blade coaters, and air doctor coaters can be used.

[0085] The release film is preferably composed of a plastic film and a release layer. Examples of plastic films include polyester films such as polyethylene terephthalate film, polybutylene terephthalate film, and polyethylene naphthalate film, and polyolefin films such as polypropylene film. The release layer can be formed, for example, from a release layer forming composition. The main components (resins) constituting the release layer forming composition are not particularly limited, but examples include silicone resins, alkyd resins, acrylic resins, and long-chain alkyl resins.

[0086] The thickness of the adhesive layer can be adjusted by the application conditions of the adhesive solution. To reduce the thickness of the adhesive layer, it is effective to reduce the application thickness.

[0087] <Image display device> An image display device according to another aspect of the present invention includes the above-described laminate. The display device is not particularly limited and includes, for example, organic EL display devices, inorganic EL display devices, liquid crystal display devices, and electroluminescent display devices. The image display device may have a touch panel function. The laminate is suitable for a flexible display having flexibility that allows it to bend or fold.

[0088] In an image display device, the laminate is positioned with its front panel facing outwards (opposite the display element side, i.e., the viewing side) and is placed on the viewing side of the display element of the image display device.

[0089] Image display devices can be used in mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signage, measuring instruments and gauges, office equipment, medical equipment, computer equipment, etc. Because distortion of reflected images on the front panel surface is suppressed, the image display device offers excellent screen visibility. [Examples]

[0090] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" refer to mass%, and parts, respectively, unless otherwise specified.

[0091] [Measurement of thickness] The thicknesses of the ultrathin glass, adhesive layer, and resin film were measured using a contact-type film thickness measuring device (Nikon Corporation's "MS-5C"). The polarizer layer and alignment layer were measured using a laser microscope (Olympus Corporation's "OLS4100").

[0092] [Measurement of storage modulus at a temperature of 25°C] The storage modulus of the adhesive layer at 25°C was measured using a viscoelasticity measuring device (Anton Paar's "MCR-301"). The adhesive layer was cut to a width of 20 mm x length of 20 mm, and multiple layers were stacked to a thickness of 150 μm. The stacked adhesive layers were then bonded to a glass plate. With the adhesive layer and the measurement chip in adhesion, measurements were taken in the temperature range of -20°C to 100°C under conditions of a frequency of 1.0 Hz, a deformation of 1%, and a heating rate of 5°C / min to determine the storage modulus at 25°C.

[0093] [Evaluation of ease of handling] After peeling the release film from the adhesive-coated laminate to expose the adhesive layer, the laminate was bonded to the polarizing film via the adhesive layer, with the phase difference plate side exposed to the substrate (PAI film). The laminate was then visually inspected to check for the presence or absence of cracks. Ten samples were evaluated for each example and comparative example. The evaluation criteria are as follows. ◎: Cracks occurred in 0-2 samples. ○: Cracks occurred in 3-4 samples. ×: Cracks occurred in 5 to 10 samples.

[0094] [Evaluation of flexibility] The release film was peeled off the adhesive layer from the laminate with the adhesive layer to expose the adhesive layer. Next, the side of the phase difference plate of the laminate with the adhesive layer that was opposite the polarizing plate was bonded to the substrate (PAI film) via the adhesive layer. A bending evaluation system (Yuasa Systems, Planar Body Unloaded U-Shape Expansion Test: DLDMLH-FS) was used. Figure 4 is a schematic diagram showing the method of this evaluation test. As shown in Figure 4, two individually movable mounting tables 401 and 402 were arranged so that the gap C was 3.0 mm (bending radius 1.5 mm), and the laminate 400 was fixed and positioned so that its widthwise center was located at the center of the gap C (Figure 4(a)). At this time, the laminate 400 was positioned so that the front plate was facing upwards. Then, the two mounting tables 401 and 402 were rotated 90 degrees upwards with positions P1 and P2 as the axis of rotation, and a bending force was applied to the region of the laminate 400 corresponding to the gap C between the mounting tables (Figure 4(b)). Subsequently, the two mounting platforms 401 and 402 were returned to their original positions (Figure 4(a)). After completing the above series of operations, the number of times bending force was applied was counted as one. This was repeated at room temperature, and then the presence or absence of cracks in the region of the laminate 400 corresponding to the gap C between the mounting platforms 401 and 402 was checked. The movement speed of the mounting platforms 401 and 402 and the pace of application of bending force were kept the same for all evaluation tests of the laminate. The criteria for counting the number of bends at which cracks occur in each laminate after bending are as follows. ○: No cracks occurred even after 200,000 bending cycles. ×: Cracks occurred after fewer than 200,000 bending cycles.

[0095] (Preparation of composition 1 for forming a hard coat layer) Composition 1 for forming a hard coat layer was prepared by dissolving 2.0 parts by mass of a dendrimer acrylate having 18 functional acrylic groups (Miramer SP1106, manufactured by Miwon Speciality Chemical), 10.0 parts by mass of a urethane acrylate having 6 functional acrylic groups (Miramer PU-620D, manufactured by Miwon Speciality Chemical), 8 parts by mass of a trifunctional acrylic group acrylate monomer (M340, manufactured by Miwon Speciality Chemical), 2 parts by mass of a photopolymerization initiator (Irgacure® 184, manufactured by BASF), and 0.1 parts by mass of a leveling agent (BYK-UV3530, manufactured by BYK Chemie Japan Co., Ltd.) in 70 parts by mass of methyl ethyl ketone (MEK) and stirring and mixing.

[0096] (Preparation of composition 2 for forming a hard coat layer) Composition 2 for forming a hard coat layer was obtained by stirring and mixing 30 parts by mass of polyfunctional acrylate (Miramer M340, manufactured by Miwon Specialty Chemical), 50 parts by mass of a propylene glycol monomethyl ether dispersion of nanosilica sol (12 nm, 40% solids content), 17 parts by mass of ethyl acetate, 2.7 parts by mass of a photopolymerization initiator (Irgacure-184, manufactured by Ciba Corporation), and 0.3 parts by mass of a fluorine-based additive (KY1203, manufactured by Shin-Etsu Chemical Co., Ltd.).

[0097] (Preparation of front panel A) The hard coat layer forming composition 2 was applied to one side of an ultrathin glass 1 (thickness 50 μm) (UTG1), the resulting coating was dried at a temperature of 80°C for 5 minutes, and then exposed to UV light at an exposure dose of 500 mJ / cm² using a UV irradiation device (SPOTCURE SP-7, manufactured by Ushio Inc.). 2 A hard coat layer 2 (HC layer 2) was formed by irradiating with UV light (based on 365 nm). The coating was applied so that the thickness after curing was 10 μm. A front plate A was obtained having a layer structure of HC layer 2 (thickness 10 μm) / UTG1 (thickness 50 μm).

[0098] (Preparation of front panel B) Except for replacing UTG1 with ultra-thin glass 2 (30 μm thick) (UTG2) in the fabrication of front panel A, front panel B was obtained in the same manner as the fabrication of front panel A, with a layer structure of HC layer 2 (10 μm thick) / UTG2 (30 μm thick).

[0099] (Fabrication of front panel C) The hard coat layer forming composition 1 was applied to one side of the UTG1, the resulting coating was dried at a temperature of 80°C for 5 minutes, and then exposed to UV light at an exposure dose of 500 mJ / cm² using a UV irradiation device (SPOTCURE SP-7, manufactured by Ushio Inc.). 2 A hard coat layer 1 (HC layer 1) was formed by irradiating with UV light (based on 365 nm). The coating was applied so that the thickness after curing was 10 μm. Then, in the same manner, an HC layer 2 was formed on the HC layer 1 using a hard coat layer forming composition 2 so that the thickness after curing was 10 μm. In this way, a front plate C having a layer structure of HC layer 2 (thickness 10 μm) / HC layer 1 (thickness 10 μm) / UTG1 (thickness 50 μm) was obtained.

[0100] (Fabrication of front panel D) Except for changing UTG1 to UTG2 during the fabrication of front panel C, the same procedure as for front panel A was used to obtain front panel D having a layer structure of HC layer 2 (thickness 10 μm) / HC layer 1 (thickness 10 μm) / UTG2 (thickness 30 μm).

[0101] (Fabrication of front panel E) The hard coat layer forming composition 1 was applied to one side of the UTG2, the resulting coating was dried at a temperature of 80°C for 5 minutes, and then exposed to UV light at an exposure dose of 500 mJ / cm² using a UV irradiation device (SPOTCURE SP-7, manufactured by Ushio Inc.). 2 HC layer 1 was formed by irradiating with UV light (based on 365 nm). It was coated so that the thickness after curing was 10 μm. Then, in the same manner, HC layer 2 was formed on the other surface of UTG2 using hard coat layer forming composition 2 so that the thickness after curing was 10 μm. In this way, a front plate E having a layer structure of HC layer 2 (thickness 10 μm) / UTG2 (thickness 30 μm) / HC layer 1 (thickness 10 μm) was obtained.

[0102] (Making adhesive sheets) Adhesive compositions A, B, and C were prepared, each forming adhesive layers A, B, and C, respectively, in the proportions of the components shown in Table 1 below. These adhesive compositions A, B, and C were applied to the release-treated surface of a release-treated film (polyethylene terephthalate film, 38 μm thick) using an applicator so that the thickness after drying was 25 μm. The applied layers were dried at 100°C for 1 minute to obtain films having adhesive layers A, B, and C. Subsequently, another release-treated film (polyethylene terephthalate film, 38 μm thick) was laminated onto adhesive layers A, B, and C. Then, the films were cured for 7 days at a temperature of 23°C and a relative humidity of 50% RH to obtain adhesive sheets A, B, and C. Furthermore, using the same procedure, adhesive sheet D having an adhesive layer D with a thickness of 5 μm was prepared using adhesive composition C.

[0103] [Table 1]

[0104] The symbols in the monomer column of Table 1 represent the following meanings. BA: Butyl acrylate MMA: Methyl Acrylate EHA: 2-ethylhexyl acrylate AA: Acrylic acid

[0105] The following crosslinking agents and silane coupling agents were used in Table 1. Crosslinking agent: Coronate L (manufactured by Tosoh Corporation) Silane coupling agent: KBM-403 (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0106] [Fabrication of polarizing plate A] (Base film) As the base film, we prepared a triacetylcellulose (TAC) film (manufactured by Konica Minolta, Inc., 25 μm thick).

[0107] (Composition for forming alignment films) Polymer 1 is a polymer having photoreactive groups consisting of the following structural units. [ka] GPC measurements revealed that the obtained polymer 1 had a number-average molecular weight of 28,200, a Mw / Mn ratio of 1.82, and a monomer content of 0.5%. A solution of polymer 1 dissolved in cyclopentanone at a concentration of 5% by mass was used as the composition for forming the orientation film.

[0108] (Polymerizable liquid crystal compound) The polymerizable liquid crystal compounds used were the polymerizable liquid crystal compound represented by formula (1-6) [hereinafter also referred to as compound (1-6)] and the polymerizable liquid crystal compound represented by formula (1-7) [hereinafter also referred to as compound (1-7)]. [ka] [ka]

[0109] Compounds (1-6) and (1-7) were synthesized by the method described in Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).

[0110] (Dichroic pigment) For the dichroic dye, we used an azo dye described in the examples of Japanese Patent Application Publication No. 2013-101328, represented by the following formulas (2-1a), (2-1b), and (2-3a). [ka] [ka] [ka]

[0111] (Composition for forming liquid crystal hardened layer) The liquid crystal curing layer formation composition was prepared by mixing 75 parts by mass of compound (1-6), 25 parts by mass of compound (1-7), 2.5 parts by mass each of the azo dyes represented by the above formulas (2-1a), (2-1b), and (2-3a) as dichroic dyes, 6 parts by mass of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure369, manufactured by BASF Japan) as a polymerization initiator, and 1.2 parts by mass of a polyacrylate compound (BYK-361N, manufactured by BYK-Chemie) as a leveling agent with 400 parts by mass of toluene as a solvent, and stirring the resulting mixture at 80°C for 1 hour.

[0112] (Composition for protective layer (OC layer)) The protective layer composition was prepared by mixing 3 parts by mass of polyvinyl alcohol resin powder (manufactured by Kuraray Co., Ltd., average degree of polymerization 18000, product name: KL-318) and 1.5 parts by mass of polyamide epoxy resin (crosslinking agent, manufactured by Sumika Chemtex Co., Ltd., product name: SR650(30)) with 100 parts by mass of water.

[0113] (Preparation of polarizing film) The substrate film was subjected to corona treatment. The corona treatment conditions were an output of 0.3 kW and a processing speed of 3 m / min. Subsequently, the alignment film-forming composition was applied to the substrate film by bar coating and heated and dried in an 80°C drying oven for 1 minute. The resulting dried film was subjected to polarized UV irradiation treatment to form an alignment film. The polarized UV treatment involved transmitting light from a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Inc.) through a wire grid (UIS-27132##; manufactured by Ushio Inc.) and measuring the integrated light amount at a wavelength of 365 nm to 100 mJ / cm². 2 The experiment was conducted under the following conditions. The thickness of the alignment film was 100 nm.

[0114] A liquid crystal curing layer-forming composition was applied to the formed alignment film by bar coating, heated and dried in a 120°C drying oven for 1 minute, and then cooled to room temperature. Using the above UV irradiation device, an integrated light intensity of 1200 mJ / cm² was applied. 2 A liquid crystal curing layer (polarizing film) was formed by irradiating the dried film with ultraviolet light at a 365 nm reference. The thickness of the obtained liquid crystal curing layer was measured using a laser microscope (OLS3000, manufactured by Olympus Corporation) and was found to be 1.8 μm. In this way, a laminated film A having a layer structure of substrate film / alignment film / liquid crystal curing layer was obtained.

[0115] A protective layer (OC layer) composition was applied to the formed liquid crystal cured layer by bar coating, and the coating was applied to a thickness of 1.0 μm after drying, and dried at a temperature of 80°C for 3 minutes. In this way, a polarizing plate A consisting of a base film, alignment film, liquid crystal cured layer, and protective layer (OC layer) was obtained.

[0116] [Fabrication of polarizing plate B] (protective layer) A cycloolefin polymer (COP) film (ZF-14, manufactured by Zeon Corporation, 23 μm thick) was prepared as a protective layer.

[0117] (Polarizing film) A long roll of polyvinyl alcohol (PVA) raw film with a thickness of 30 μm [product name "Kuraray Poval Film VF-PE#3000" manufactured by Kuraray Co., Ltd., average degree of polymerization 2400, degree of saponification 99.9 mol% or more] was continuously conveyed while being unwound from a roll, and immersed in a swelling bath consisting of pure water at 20°C for a residence time of 31 seconds (swelling process). Subsequently, the film removed from the swelling bath was immersed in a dyeing bath at 30°C containing iodine in a potassium iodide / water ratio of 2 / 100 (by weight) for a residence time of 122 seconds (dyeing process). Next, the film removed from the dyeing bath was immersed in a 56°C crosslinking bath with potassium iodide / boric acid / water in a weight ratio of 12 / 4.1 / 100 for a residence time of 70 seconds, and then immersed in a 40°C crosslinking bath with potassium iodide / boric acid / water in a weight ratio of 9 / 2.9 / 100 for a residence time of 13 seconds (crosslinking process). In the dyeing and crosslinking processes, longitudinal uniaxial stretching was performed by stretching between rolls in the bath. The total stretching ratio based on the original film roll was 5.4 times. Next, the film removed from the crosslinking bath was immersed in a washing bath consisting of 5°C pure water for a residence time of 3 seconds (washing process), and then introduced into a first heating furnace with humidity control for high temperature and high humidity treatment for a residence time of 190 seconds (high temperature and high humidity treatment process) to obtain a polarizing film (PVA) with a thickness of 12.1 μm.

[0118] (Adhesive composition) An adhesive composition was obtained by mixing 100 parts by weight of water, 3 parts by weight of polyvinyl alcohol resin powder (manufactured by Kuraray Co., Ltd., average degree of polymerization 18000, product name: KL-318), and 1.5 parts by weight of polyamide epoxy resin (crosslinking agent, manufactured by Sumika Chemtex Co., Ltd., product name: SR650(30)).

[0119] The polarizing film and protective layer were subjected to corona treatment. The corona treatment conditions were an output of 0.3 kW and a processing speed of 3 m / min. Subsequently, these were bonded together via an adhesive composition and dried at 60°C for 2 minutes to obtain a polarizing plate B consisting of a protective layer and a polarizer layer.

[0120] [Fabrication of phase difference plates] (1st liquid crystal hardening retardation layer) As the first liquid crystal cured phase difference layer, a layer providing a λ / 4 phase difference was prepared, consisting of a cured nematic liquid crystal compound layer, an alignment layer, and a transparent substrate. The total thickness of the cured nematic liquid crystal compound layer and the alignment layer was 2 μm. The cured nematic liquid crystal compound layer was formed by coating an alignment layer formed on a substrate film (transparent substrate) with a phase difference layer forming composition containing the nematic liquid crystal compound and then curing it.

[0121] (Second liquid crystal hardening retardation layer) A polyethylene terephthalate substrate with a thickness of 38 μm is used as the base film (transparent substrate), and a composition for vertical orientation is coated on one side thereof to a thickness of 3 μm, with a concentration of 20 mJ / cm². 2 An orientation layer was prepared by irradiating it with polarized ultraviolet light. The composition for the vertical orientation layer was a mixture of 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, dipentaerythritol triacrylate, and bis(2-vinyloxyethyl) ether in a ratio of 1:1:4:5, with 4% of LUCIRIN® TPO added as a polymerization initiator.

[0122] Next, a phase difference layer forming composition containing a photopolymerizable nematic liquid crystal (Merck, RMM28B) was coated onto the formed alignment layer by die coating. In this liquid crystal composition, a mixed solvent was used, consisting of methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone (CHN) with a boiling point of 155°C, mixed in a mass ratio (MEK:MIBK:CHN) of 35:30:35. Then, the phase difference layer forming composition, prepared to have a solid content of 1 to 1.5 g, was coated onto the alignment layer in a wet amount of 4 to 5 g.

[0123] After coating the alignment layer with a composition for forming a phase difference layer, a drying treatment was performed at a drying temperature of 75°C for a drying time of 120 seconds. Subsequently, the liquid crystal compound was polymerized by ultraviolet (UV) irradiation to obtain a positive C layer consisting of a layer of cured photopolymerizable nematic liquid crystal compound, an alignment layer, and a transparent substrate. The total thickness of the layer of cured photopolymerizable nematic liquid crystal compound and the alignment layer was 4 μm.

[0124] (Fabrication of phase difference plate) The first liquid crystal cured phase difference layer and the second liquid crystal cured phase difference layer were bonded together using an ultraviolet-curable adhesive, with the surfaces of each liquid crystal cured phase difference layer (the surfaces opposite to the transparent substrate) serving as the bonding surfaces. Next, the ultraviolet-curable adhesive was cured by irradiation with ultraviolet light. The thickness of the adhesive after curing was 2 μm. In this way, a phase difference plate having a layer structure of substrate film / alignment layer / first liquid crystal cured phase difference layer (2 μm) / adhesive layer (thickness 2 μm) / second liquid crystal cured phase difference layer (thickness 4 μm) / alignment layer / substrate film was fabricated.

[0125] <Example 1> The adhesive layer D, exposed by peeling off one of the release films from the adhesive sheet D, was bonded to the protective layer side of the polarizing plate A to obtain a laminate A1. The bonding surface was pre-treated with double-sided corona treatment (output 0.3kW, speed 3m / min).

[0126] The base film on the first liquid crystal cured phase difference layer side of the phase difference plate was peeled off, and the other release film was peeled off from laminate A1 to expose the adhesive layer D. Furthermore, the adhesive layer D of laminate A1 and the first liquid crystal cured phase difference layer of the phase difference plate were bonded together to obtain laminate A2. The bonding surface was pre-treated with double-sided corona treatment (output 0.3kW, speed 3m / min).

[0127] One release film was peeled off from adhesive sheet A to expose the adhesive layer A. Next, the exposed adhesive layer A was bonded to the surface from which the base film used to form the second liquid crystal curing phase difference layer was peeled off from laminate A2 to obtain laminate A3. The bonding surface was pre-treated with double-sided corona treatment (output 0.3kW, speed 3m / min).

[0128] One release film was peeled off from another adhesive sheet A (referred to as adhesive sheet A') to expose the adhesive layer A (referred to as adhesive layer A'). Next, the exposed adhesive layer A' was bonded to the UTG side of the front panel to obtain laminate A4. The bonding surface was pre-treated with double-sided corona treatment (output 0.3kW, speed 3m / min).

[0129] The release film of laminate A4 was peeled off to expose the adhesive layer A'. Next, the adhesive layer A' of laminate A4 was bonded to the base film side of polarizing plate A of laminate A3 to obtain a laminate with an adhesive layer. The bonding surface was pre-treated with double-sided corona treatment (output 0.3kW, speed 3m / min). The results are shown in Table 2.

[0130] <Examples 2-6 and Comparative Examples 1-4> A laminate with an adhesive layer was obtained in the same manner as in Example 1, except that the types of front plate, polarizing film, and adhesive layer shown in Table 1 were used for the front plate, polarizing film, and adhesive layer used to bond the front plate and polarizing film. In Example 5, adhesive layer A was bonded to the HC layer 1 side of the front plate. In Comparative Examples 1 and 2, UTG1 and UTG2 were used as front plates without forming a hard coat layer, respectively. Furthermore, in Comparative Example 5, the adhesive layer was directly bonded to polarizing film B. The results are shown in Table 2.

[0131] [Table 2] [Explanation of Symbols]

[0132] 100,200,300,400 Laminate, 10,21 Front plate, 11,22 Adhesive layer, 12,23 Polarizing plate, 13 Hard coat layer, 14,28 Ultra-thin glass, 24 Laminating layer, 25 Phase difference plate, 26 First hard coat layer, 27 Second hard coat layer, 15,29 Base film, 16,30 Alignment film, 17,31 Polarizing film (Liquid crystal hardened layer), 18,32 Protective layer, 33 First liquid crystal hardened phase difference layer, 34 Second liquid crystal hardened phase difference layer, 401,402 Mounting stage.

Claims

1. The front plate includes a front plate, a pressure-sensitive adhesive layer, and a polarizing film in this order. The front plate includes ultra-thin glass and a hard coat layer, The pressure-sensitive adhesive layer has a storage modulus of 0.2 MPa or less at a temperature of 25° C., The polarizing film is a laminate constituted by a liquid crystal cured layer containing a cured product of a polymerizable liquid crystal compound.

2. 2. The laminate of claim 1, wherein the ultra-thin glass has a thickness of 50 μm or less.

3. The laminate according to claim 1 , wherein the hard coat layer has a thickness of 10 μm or more.

4. The laminate according to claim 2 , wherein the hard coat layer has a thickness of 10 μm or more.

5. The laminate according to any one of claims 1 to 4, wherein the pressure-sensitive adhesive layer has a storage modulus of 0.01 MPa or more at a temperature of 25°C.

6. The laminate according to any one of claims 1 to 4, wherein the pressure-sensitive adhesive layer has a thickness of 30 µm or less.

7. The laminate according to claim 5 , wherein the pressure-sensitive adhesive layer has a thickness of 30 μm or less.

8. A laminate described in any one of claims 1 to 4, wherein the hard coat layer has a multilayer structure consisting of two or more layers.

9. A laminate described in any one of claims 1 to 4, which, when repeatedly bent with a bending radius of 1.5 mm, causes the first crack to occur after 200,000 or more bends.

10. The laminate described in claim 8, which, when repeatedly bent with a bending radius of 1.5 mm, causes the first crack to appear after 200,000 or more bends.

11. An image display device comprising the laminate according to any one of claims 1 to 4.